2020
DOI: 10.1177/1536012120939398
|View full text |Cite
|
Sign up to set email alerts
|

Two Patient Studies of a Companion Diagnostic Immuno-Positron Emission Tomography (PET) Tracer for Measuring Human CA6 Expression in Cancer for Antibody Drug Conjugate (ADC) Therapy

Abstract: An antigen binding fragment (BFab) derived from a tumor-associated mucin 1–sialoglycotope antigen (CA6) targeting antibody (huDS6) was engineered. We synthesized a companion diagnostic positron emission tomography (PET) tracer by radiolabeling BFab with [64Cu] to measure CA6 expression on cancer tissues prior to anti-human CA6 (huDS6-DM4 antibody-drug conjugate) therapy for ovarian and breast cancer patients. After chemotherapy, the ovarian patient received PET scan with 18F-2-fluoro-2-deoxyglucose ([18F]FDG: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Additionally, an 89 Zr-labeled anti-MUC1 or CA 15-3 also showed proper performance in vivo ( 37 ). The first clinical study on a Fab targeting carbonic anhydrase 6 (CA6) epitope of MUC1 reported the safety of this probe in an ovarian cancer patient, and the probe correctly reflected the low tumor expression of CA6 observed in IHC ( 370 ).…”
Section: Immunopet In Different Malignanciesmentioning
confidence: 99%
“…Additionally, an 89 Zr-labeled anti-MUC1 or CA 15-3 also showed proper performance in vivo ( 37 ). The first clinical study on a Fab targeting carbonic anhydrase 6 (CA6) epitope of MUC1 reported the safety of this probe in an ovarian cancer patient, and the probe correctly reflected the low tumor expression of CA6 observed in IHC ( 370 ).…”
Section: Immunopet In Different Malignanciesmentioning
confidence: 99%
“…The species Cu-ATSM, with ATSM being diacetylbis(4-methyl-3-thiosemicarbazone), is not only under phase 2 of clinical trials for the treatment of rectal cancer (NCT03951337) [25], but has also progressed to phase 2/3 (NCT04082832) for its use against the neurodegenerative disease amyotrophic lateral sclerosis [31]. The complex 64 Cu-DOTA, where DOTA is 2,2 ′ ,2 ′′ ,2 ′′′ -(1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrayl)tetraacetate, reached phase 1 (NCT02708511) for positron emission tomographycomputed tomography use in imaging patients with ovarian and breast cancer [32]. The species Cu-histidinato is at phase 1/2 of the trials for its employment in the treatment of Menkes disease (NCT00001262).…”
Section: Introductionmentioning
confidence: 99%